An analysis of the North American market for wood scanners - Johansson, Niklas (2008)
Innovativ Vision AB develops and delivers quality and production control systems for the woodworking industry. North America is emerging as one of the most important markets for Innovativ Vision AB and their scanner WoodEye. Since 2001 Innovativ Vision AB has an office in the USA for customer service and support. In 2004 they also established a local sales and distributions office in USA. Innovativ Vision AB is in the process of developing WoodEye's new software Edger, Planer and NHLA. A market analysis is necessary in order to establish suitable plans of actions for further launching of the new software in the North American sawmill industry market.